Developing a dynamic query system on location-based services. (7th February 2006) - Weng, Sung-Shun; Chou, Yi-Chen; Lin, Binshan
This study is to develop a dynamic query system for moving objects in order to dynamically query static data based on the factors of 'moving objects', 'coordinate position', and 'time'. All stationary or moving objects in the system, becoming the users who query, can decide by themselves the starting query position, speed, duration, distance, and the queried items. Moreover, it can support: (1) multiple dynamic queries and (2) moving query range. Through the dynamic query system, it supports moving objects to query dynamically, depending on the requirements at that time, in order to obtain more accurate query results.